Chronic Modafinil Administration to Preadolescent Rats Impairs Social Play Behavior and Dopaminergic System - Renard, G; Cid-Jofre, V (Elsevier Ltd, 2021)
Some clinical trials are investigating modafinil (Mod) as a treatment for attentional deficit and hyperactivity disorder (ADHD) in children and adolescents. Mod increases dopamine (DA) levels in the reward system by blocking dopamine transporter (DAT). Social interactions are rewarding behaviors and evidence reveals the importance of reward circuitry in social interactions. Chronic psychostimulant treatments alter DA neurotransmission and associated behaviors. The aim of this work was to evaluate the effects of chronic Mod treatment during preadolescence on social play behavior, locomotor activity, and DA in nucleus accumbens (NAc). Preadolescent male Sprague-Dawley rats were injected with Mod (75 mg/kg i.p.) or vehicle for 14 days (PND22 to PND35). After that, we measured social play behavior, content and DA release in NAc by HPLC coupled to electrochemical detection, protein levels of DA type 2 receptor (D2) by Western blot and DA kinetic by fast-scan cyclic voltammetry (FSCV) in NAc. Regarding social play, the total number of pinning events decreased in the Mod group compared with the vehicle. The K+-stimulated DA release in NAc was significantly lower in Mod-treated rats compared with vehicle group. Also, Mod increases locomotor activity at the first injection, but this effect is almost completely lost at day 14 of Mod treatment. Chronic Mod treatment during preadolescence in rats impairs dopaminergic neurotransmission in NAc and decreases the capacity of rats to perceive rewarding effects of social play. Importantly, as Mod is being evaluated to treat ADHD in children and adolescents, potential effects on social behavior should be considered since this kind of behavior in this particular stage is crucial for neurodevelopment. © 2020 Elsevier Ltd